Probing electron correlation through radiative lifetime measurements upon inner-valence photoionization of Ne and Ar. (15th June 2016) - Suzuki, Norihiro; Kosugi, Satoshi; Ito, Yumi; Inoue, Naoki; Nagoshi, Tatsuro; Kuze, Nobuhiko; Harries, James R; Sullivan, James P; Nagata, Tetsuo; Sokell, Emma; Koike, Fumihiro; Azuma, Yoshiro
Abstract: This work demonstrates that electron correlation can have a strong effect on the radiative lifetime of atoms. We report measurements of the radiative lifetimes of inner-valence hole states, the 3s3p 6 2 S1/2 state of Ar + and the 2s2p 6 2 S1/2 state of Ne + by using the time-correlated single photon counting technique combined with photoionization by synchrotron radiation. Theoretical calculations utilizing the multi-configuration Dirac–Fock method agreed well with the experimental results. In particular, the radiative lifetime was found to depend very sensitively on the mixing of valence excited state configurations. While the Ne + 2s2p 6 2 S1/2 state only has relatively weak inter-shell correlation, Ar + 3s3p 6 2 S1/2 state has strong intra-shell correlation within the M-shell. This intra-shell correlation enhances configuration mixing and causes the radiative lifetime of the Ar + 3s3p 6 2 S1/2 state to become very much longer than that of the Ne + 2s2p 6 2 S1/2 state.